Ownership of health financing policies in low-income countries: a journey with more than one pathway - Kiendrébéogo, Joël; Meessen, Bruno (BMJ global health, 2019)
Summary box - - There is broad international consensus that weak governmental ownership can compromise the long-term sustainability of development policies in low-income countries (LICs).1 Ownership has thus become a cornerstone of official development assistance, as evidenced by the prominent place it occupies in international resolutions such as the Paris Declaration (2005), the Accra Agenda for Action (2008) and the Busan Partnership for Effective Development Cooperation (2011). Despite this strong signal, coming from both donors and ‘recipient’ countries, problems persist, especially in Africa.2 3 - - Ownership is an elusive concept. The Paris Declaration attempted to assess it by the ‘number of countries with national operational development strategies that have clear strategic priorities linked to a medium-term expenditure framework and reflected in annual budgets’; but this indicator proved disappointing.4 Ownership can be approached through different perspectives (eg, ‘governmental ownership’, ‘country ownership’ or ‘democratic ownership’).5 In this commentary, we will focus on ‘country ownership’ of health financing policies which, unlike ‘governmental ownership’, is much broader as it also …